Vanishing of the first (σ, τ)-cohomology group of triangular Banach algebras - Motlagh, A. N.; Moslehian, M. S.; Khosravi, M. (Methods of Functional Analysis and Topology, 2008)
In this paper, we define the first topological (σ,τ)-cohomology group and examine vanishing of the first (σ,τ)-cohomology groups of certain triangular Banach algebras. We apply our results to study the (σ,τ)-weak amenability and (σ,τ)-amenability of triangular Banach algebras.